2013
DOI: 10.1007/s10903-013-9955-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Networks: Cardiovascular Responses Following Recall on Immigration Stress Among Chinese Americans

Abstract: Social support has been shown to act as a buffer for cardiovascular responses to stress. However, little is known about how social support and networks are related to cardiovascular responses to immigration stress recall. The current study evaluated the impact of structural and functional support on cardiovascular reaction following immigrant stress recall provocation as well as the moderation effect of interdependent self-construal among first-generation Chinese immigrants. One hundred fifty Chinese immigrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Similarly, not all studies find a buffering effect of social support on CVR, rather, some find that support can be associated with higher CVR (Lee et al, 2015;Roy et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, not all studies find a buffering effect of social support on CVR, rather, some find that support can be associated with higher CVR (Lee et al, 2015;Roy et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Collectivism is one of the core elements of Chinese culture. 16 To Chinese immigrants, peer learning experiences and group learning environments are crucial and lead to success. This finding is congruent with Lee et al 's study, 16 in which collectivism was found to be related to physiological responses to stress among first-generation Chinese immigrants.…”
Section: Discussionmentioning
confidence: 99%
“… 16 To Chinese immigrants, peer learning experiences and group learning environments are crucial and lead to success. This finding is congruent with Lee et al 's study, 16 in which collectivism was found to be related to physiological responses to stress among first-generation Chinese immigrants. Learning in a group is appealing to Chinese Americans not only because they can gain empirical self-management skills from others, but also due to their willingness to help peers by discussing their personal experiences.…”
Section: Discussionmentioning
confidence: 99%
“…For depressive symptoms , we used the Depression Inventory Short Version (CDI-S; Kovacs, 1992). The Spanish version by Del Barrio and Carrasco (2004) was used.…”
Section: Methodsmentioning
confidence: 99%